ISO 13485:2016 : a complete guide to quality management in the medical device industry - Abuhav, Itay (CRC Press, Taylor & Francis, 2018)
"This book will be a substantial revision, which will reflect the new version of the ISO 13485:2016. This represents the standard protocols that all medical device manufacturers must follow, in the fabrication of their products. It will focus on changes in the structure of the quality management system; change in the documentation for quality managemeent systems and finally, present the different methods of implementation of the standard requirements within the organization. This new version was initiated in 2016, thus all apprpriate enterprises using the old standard must convert to the new version, now available. The Second Edition will clarify, explain and demonstrate the new version."--